China as a national security threat: A comparative study of changing threat perceptions in the Baltic Sea region - Andreas Bøje Forsby (Danish Institute for International Studies (DIIS), 2021)
As the rise of China is increasingly viewed as a security-related threat, Europe's engagement with China is entering a new phase. This report investigates emerging threat perceptions of China in the Baltic Sea region, focusing specifically on six liberal small states: Denmark, Estonia, Finland, Latvia, Lithuania and Sweden. Conducting a comparative analysis of the past five-year period, the report identifies differences and similarities in emerging threat perceptions and provides an overview of bilateral relations between China and each of the six countries. Specifically, the report examines the securitization of 5G and Huawei and the extraordinary measures adopted by these countries to protect their critical digital infrastructures from any risk of Chinese influence. While the six countries far from constitute a uniform block - as testified, for instance, by Finland and Lithuania's rather different approaches - the report documents how all six countries, notably since 2019, have seen a significant deterioration of their relationship with China as security-related concerns and sensitive political issues have come to dominate the bilateral agenda. Moreover, the report finds that the deterioration of bilateral relationships has primarily been prompted by the dramatic shift in 2018 in the Trump administration's China policy as well as the hardening of the Chinese regime under Xi Jinping, in particular since 2019 as manifested by the systematic violations of liberal human rights in Hong Kong and Xinjiang.
Keywords: 300